Ag-functionalized nanocrystalline cellulose for paper preservation and strengthening. (1st March 2020) - Bergamonti, Laura; Potenza, Marianna; Haghighi Poshtiri, Azar; Lorenzi, Andrea; Sanangelantoni, Anna Maria; Lazzarini, Laura; Lottici, Pier Paolo; Graiff, Claudia
Highlights: Waste paper was used to obtain nanocrystalline cellulose (CNC). The obtained CNC was compared with CNC from cotton linter. The biocidal activity of CNC added with Ag nanoparticles was assessed. The growth of Aspergillus niger on Whatman paper is inhibited by CNC/Ag coating. The mechanical properties of Whatman paper improve by the CNC coatings. Abstract: Waste paper is an environmentally friendly source of cellulosic material. Here we propose a new treatment based on nanocrystalline cellulose (CNC) for paper preservation and consolidation. Suspensions of CNC were prepared by sulfuric acid hydrolysis using waste paper as cellulose source (CNCWP ) and compared with CNC from cotton linter (CNCCL ). Both CNCs were obtained with good yield, showing high crystallinity index and comparable morphology, as demonstrated by DLS-ELS, XRD, FTIR, Raman and TEM analyses. CNCs were mixed with silver nanoparticles (CNC/Ag) and their biocidal activity was tested against Escherichia coli and Bacillus subtilis, measuring the minimum inhibitory concentration. CNCs were exploited as treatments for biocidal activity and consolidation on Whatman paper. The presence of silver nanoparticles doesn't affect aesthetic appearance of the original paper and prevents the growth of Aspergillus niger fungus. Mechanical tests demonstrated that the coatings by CNC based products improve stretch and toughness of the paper support.